Mechanism of Hydrophobic Bile Acid-Induced Hepatocyte Injury and Drug Discovery - Wei, Shizhang; Ma, Xiao; Zhao, Yanling (Frontiers in Pharmacology, 2020)
Cholestatic liver disease is caused by the obstruction of bile synthesis, transport, and excretion in or outside the liver by a variety of reasons. Long-term persistent cholestasis in the liver can trigger inflammation, necrosis, or apoptosis of hepatocytes. Bile acid nuclear receptors have received the most attention for the treatment of cholestasis, while the drug development for bile acid nuclear receptors has made considerable progress. However, the targets regulated by bile acid receptor drugs are limited. Thus, as anticipated, intervention in the expression of bile acid nuclear receptors alone will not yield satisfactory clinical results. Therefore, this review comprehensively summarized the literature related to cholestasis, analyzed the molecular mechanism that bile acid damages cells, and status of drug development. It is hoped that this review will provide some reference for the research and development of drugs for cholestasis treatment in the future.